113k views
1 vote
Evaluate (pictured below)

Evaluate (pictured below)-example-1

1 Answer

2 votes
The exponential term dominates, so that the limit is 0.

To see why: Suppose we take
y=-x, so that as
x\to-\infty we have
y\to+\infty. Now


\displaystyle\lim_(x\to-\infty)x^4e^x=\lim_(y\to+\infty)(-y)^4e^(-y)=\lim_(y\to+\infty)(y^4)/(e^y)

Now recall that for all
y>0, we have
y>\ln y, which means
e^y>y. We can similarly argue that for sufficiently large values of
y, we have
e^y>y^n for all integers
n. So the denominator in the limit with respect to
y will always (eventually) exceed the numerator and make the entire expression approach 0.
User Nicolas D
by
5.1k points